Exploring the Impact of Conformity on Impulsive Buying: Implications for Counseling Practices - Lospabai, Henkbajeck Jomn; Soetjiningsih, Christiana Hari (Jurnal Bimbingan dan Konseling Terapan, 2024)
Given the increasing prevalence of impulsive buying behavior among football supporters, understanding the underlying social influences becomes crucial for effective intervention. This study examines the relationship between conformity and impulsive buying behavior among football supporters in Salatiga. Using a quantitative correlational design, data was collected from 106 participants via an online questionnaire distributed through social media. The findings reveal a significant positive relationship between conformity and impulsive buying, with 49.1% of participants exhibiting high conformity and 55.7% displaying high impulsive buying behavior. The effective contribution of conformity to impulsive buying was 82%, indicating that peer pressure and social dynamics significantly influence buying behavior. The study suggests that counselors should develop targeted interventions to help individuals manage conformity pressures, enhance self-awareness, and make more rational purchasing decisions. The research highlights the need for financial literacy education and supportive group counseling sessions to address the psychological and practical aspects of impulsive buying. However, the study's limitations include its focus on a specific demographic and potential biases in self-reported data, necessitating further research to generalize the findings.